Hypocretin/orexin influences chronic sleep disruption injury in the hippocampus - Nick, Henry; Fenik, Polina; Zhu, Yan; Veasey, Sigrid (Frontiers in Aging Neuroscience, 2022)
Chronic sleep disruption is a risk factor for Alzheimer’s disease (AD), yet mechanisms by which sleep disturbances might promote or exacerbate AD are not understood. Short-term sleep loss acutely increases hippocampal amyloid  (A) in wild type (WT) mice and long-term sleep loss increases amyloid plaque in AD transgenic mouse models. Both effects can be influenced by the wake-promoting neuropeptide, hypocretin (HCRT), but whether HCRT influences amyloid accumulation independent of sleep and wake timing modulation remains unclear. Here, we induced chronic fragmentation of sleep (CFS) in WT and HCRT-deficient mice to elicit similar arousal indices, sleep bout lengths and sleep bout numbers in both genotypes. We then examined the roles of HCRT in CFS-induced hippocampal A accumulation and injury. CFS in WT mice resulted in increased A42 in the hippocampus along with loss of cholinergic projections and loss of locus coeruleus neurons. Mice with HCRT deficiency conferred resistance to CFS A42 accumulation and loss of cholinergic projections in the hippocampus yet evidenced similar CFS-induced loss of locus coeruleus neurons. Collectively, the findings demonstrate specific roles for orexin in sleep disruption hippocampal injury.